Down Syndrome Fetal Fibroblasts Display Alterations of Endosomal Trafficking Possibly due to SYNJ1 Overexpression - De Rosa, Laura; Fasano, Dominga; Zerillo, Lucrezia; Valente, Valeria; Izzo, Antonella; Mollo, Nunzia; Amodio, Giuseppina; Polishchuk, Elena; Polishchuk, Roman; Melone, Mariarosa Anna Beatrice; Criscuolo, Chiara; Conti, Anna; et al. (Frontiers in Genetics, 2022)
Endosomal trafficking is essential for cellular homeostasis. At crossroads of distinct intracellular pathways, the endolysosomal system is crucial to maintain critical functions and adapt to the environment. Alterations of endosomal compartments were observed in cells from adult individuals with Down Syndrome (DS), suggesting that the dysfunction of the endosomal pathway may contribute to DS pathogenesis. However, the nature and the degree of impairment as well as the timing of onset remain elusive. Here, by applying imaging and biochemical approaches, we demonstrate that the structure and dynamics of early endosomes are altered in DS cells. Furthermore, we found that recycling trafficking is markedly compromised in these cells. Remarkably, our results in 18-20 week-old human foetal fibroblasts indicate that alterations in the endolysosomal pathway are already present early in development. In addition, we show that overexpression of the polyphosphoinositide phosphatase synaptojanin 1 (Synj1) recapitulates the alterations observed in DS cells, suggesting a role for this lipid phosphatase in DS pathogenesis, likely already early in disease development. Overall, these data strengthen the link between endolysosomal pathway and DS, highlighting a dangerous liaison among Synj1, endosomal trafficking and Down syndrome.